Simplification of Soil Maps Information Using Geographic Information Systems - Elkhboli, M. M. H. (Al-Mukhtar Journal of Sciences, 2007)
Geographic Information Systems (GIS) was used to simplify the information of soil maps considered important for users who have different needs and objectives, whether they plan to use new lands for agricultural purposes or to improve on the existing agricultural production. Simplified maps were produced using ArcView GIS 3.2 and its associated software through several steps. Digital and text data were saved and connected with its spatial (geographical) sites. In addition to that, a number of soil properties such as soil depth, soil texture, rock fragments and soil erosion were separated from the compound soil map. Furthermore, soil classification map was produced according to the American system. It includes three soil types (Alfisols, Mollisols, and Inceptisols) and three sub-types (Xeralfs, Rendolls and Ocherpts) and five great groups as well as nine sub-great groups.